2021
DOI: 10.1111/jpc.15349
|View full text |Cite
|
Sign up to set email alerts
|

Investigating paediatric hypoglycaemia: Dynamic studies at a tertiary paediatric hospital

Abstract: Aim Paediatric hypoglycaemia often requires specific investigations to determine aetiology. Samples from the time of hypoglycaemia may not be available and a diagnostic fasting test may be required. Additionally, fasting studies can determine safe fasting intervals and prolonged oral glucose challenges can assess hypoglycaemia due to abnormal post‐prandial glucose handling. This audit reviewed the current utility and yield of fasting studies, prolonged oral glucose challenges and starch loads. Methods Retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…More recently Graves et al. showed that 4/91 fasting challenges performed in children with suspected or documented hypoglycemia resulted in an etiological diagnosis (i.e., hepatic GSD, partial ACTH deficiency, panhypopituitarism, isolated central hypothyroidism) ( 31 ).…”
Section: Functional In Vivo Testsmentioning
confidence: 99%
“…More recently Graves et al. showed that 4/91 fasting challenges performed in children with suspected or documented hypoglycemia resulted in an etiological diagnosis (i.e., hepatic GSD, partial ACTH deficiency, panhypopituitarism, isolated central hypothyroidism) ( 31 ).…”
Section: Functional In Vivo Testsmentioning
confidence: 99%